Protecting the Customary Land Rights of the Laman Kinipan Indigenous Community: A Responsive Law Perspective - Aditya Riza Dharmawan; Faiz Rahmanto; Dimas Abi Galoga Dasopang (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
The protection of indigenous communal land rights should be ensured through constitutional recognition, legal certainty, and meaningful participation of indigenous peoples in decision-making processes concerning their customary territories. However, the reality of the conflict between the Laman Kinipan Indigenous Community and a palm oil plantation company demonstrates that legal protection remains ineffective due to conditional legal recognition, unequal power relations, and the limited implementation of indigenous participation in licensing procedures. This study aims to analyze the protection of the communal land rights of the Laman Kinipan Indigenous Community from the perspective of responsive law and to examine the Free, Prior and Informed Consent (FPIC) principle as a normative instrument for strengthening the protection of indigenous peoples' rights. This research employs a normative juridical method using statutory, case, and conceptual approaches based on secondary legal materials, including legislation, court decisions, and relevant scholarly literature. The findings reveal that the protection of communal land rights has not been effectively implemented because the existing legal framework still reflects a repressive legal orientation. Therefore, strengthening legal protection requires harmonizing agrarian and sectoral regulations, reinforcing the administrative recognition of indigenous communities, institutionalizing FPIC as a substantive licensing requirement, and developing a more responsive agrarian legal framework to ensure justice and legal certainty for indigenous peoples.